KODE ETIK YANG BERLAKU DALAM KEGIATAN PEMOLISIAN MASYARAKAT - Cindi Indriani; Merliana Elisa Putri, Pandu Caesaryo Dwi Saputra, Yemima Priscila Barutu, Tugimin Supriyadi (CAPITALIS: JOURNAL OF SOCIAL SCIENCES, 2024)
Policing is a proactive initiative by the Indonesian National Police (Polri) focusing on collaboration between police and the community to prevent crime and address social issues through the Community Policing Program (Polmas). The aim of this research is to determine the applicable code of ethics in community policing activities. The method used in this study employs library research. The police code of ethics provides moral and professional guidance for police officers to carry out their duties with integrity, professionalism, social responsibility, and respect for human rights. By adhering to this code of ethics, police can build strong and trusting relationships with the communities they serve, maintain the credibility of the police institution, and provide the best service to the public. The code of ethics applicable to community policing activities is an essential moral and professional guide for every officer in performing their duties with integrity, professionalism, social responsibility, respect for human rights, transparency, and accountability. By following this code of ethics, police can maintain the reputation and credibility of their institution, provide the best service to the community, and build strong and trusting relationships with the communities they serve.